2008
DOI: 10.1083/jcb.200711002
|View full text |Cite|
|
Sign up to set email alerts
|

Prion protein attenuates excitotoxicity by inhibiting NMDA receptors

Abstract: It is well established that misfolded forms of cellular prion protein (PrP [PrPC]) are crucial in the genesis and progression of transmissible spongiform encephalitis, whereas the function of native PrPC remains incompletely understood. To determine the physiological role of PrPC, we examine the neurophysiological properties of hippocampal neurons isolated from PrP-null mice. We show that PrP-null mouse neurons exhibit enhanced and drastically prolonged N-methyl-d-aspartate (NMDA)–evoked currents as a result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
221
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(237 citation statements)
references
References 50 publications
(68 reference statements)
16
221
0
Order By: Relevance
“…A less likely alternative is that ⌬CR PrP activates a ubiquitously expressed, endogenous ion channel. There is evidence that PrP functionally and physically interacts with certain types of ionotropic glutamate receptors (45) and that neurons from PrP knock-out mice display several kinds of electrophysiological abnormalities (46 -49). However, the nature of the interactions between PrP and endogenous ion channels remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A less likely alternative is that ⌬CR PrP activates a ubiquitously expressed, endogenous ion channel. There is evidence that PrP functionally and physically interacts with certain types of ionotropic glutamate receptors (45) and that neurons from PrP knock-out mice display several kinds of electrophysiological abnormalities (46 -49). However, the nature of the interactions between PrP and endogenous ion channels remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, neurons from PrP-null mice have been reported to display various kinds of electrophysiological abnormalities (52)(53)(54)(55). It has been suggested that PrP C specifically suppresses the activity of a subclass of NMDA-type glutamate receptors based on the demonstration that PrP C physically interacts with the NR2D subunit of these receptors and the fact that neurons from Prn-p Ϫ/Ϫ mice showed enhanced NMDA-evoked currents and were more susceptible to glutamate-induced excitotoxic death (56). Taken together with our observation that WT PrP silences the currents induced by ⌬CR PrP, the available evidence suggests a possible physiological role for PrP C in regulation of several kinds of ion channels.…”
Section: Biophysical Characteristics and Molecular Basis Of ⌬Cr Prp-imentioning
confidence: 99%
“…For instance, PrP C has been involved in the inhibition of excitotoxicity mediated by the N-methyl-D-aspartate receptor (NMDAR). 81 It has been hypothesized that this regulation is executed either through direct interaction of PrP C with NMDAR subunits (PrP C co-immunoprecipitates with the NR2D subunit of the NMDAR) or via protein kinases 82 such as the Src tyrosine kinase family member Fyn. 83 Of note, NMDARs localize in lipid raft domains but can also be present in non-raft domains after phosphorylation.…”
Section: 74mentioning
confidence: 99%